Exploring athlete burnout: the interplay among psychological factors in elite Italian athletes - Valdesalici, A.; Ghisi, M.; Borella, E. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Athletes are routinely exposed to different stressors that can potentially undermine their well-being and cause negative consequences such as sport performance decrements, burnout, and drop-out. Athlete burnout (AB) is a multidimensional syndrome characterized by physical and emotional exhaustion (PEE), sport devaluation (SD), and reduced sense of accomplishment (RSA). Numerous psychological factors are implicated in AB, nevertheless, the interplay between AB and individual psychological factors and sport-related situational variables remains unexplored. This study aims to investigate AB prevalence and severity in Italian elite athletes and explore the possible different impacts of distress, resilience, motivational orientation, and motivational climate on the three dimensions of AB. METHODS: A total of 107 elite athletes (Age: M=22.99, SD=4.06; Female: n=60) engaging in individual and team sports like basketball, rugby, volleyball, athletics, and fencing, and competing at regional, national, and international levels were recruited for the present study. Athletes completed a series of online questionnaires investigating resilience (Connor-Davidson Resilience Scale-10, CD-RISC-10), distress (Depression Anxiety Stress Scales-21, DASS-21), motivational orientation and motivational climate (Task and Ego Orientation in Sport Questionnaire, TEOSQ; Perceived Motivational Climate in Sport Questionnaire, PMCSQ), and burnout (Athlete Burnout Questionnaire, ABQ). RESULTS: According to the regression analyses, no socio-demographic characteristic (i.e., age, gender, years of experience) was implicated in AB. Nevertheless, the investigated psychological and situational variables showed different associations with the three dimensions of AB. Specifically, resilience, distress, motivational orientation, and motivational climate explained 15% of variance in PEE dimension of AB (p=0.011), with distress (b=0.028, p=0.003) and performance-oriented motivational climate (b=0.044, p=0.033) resulting as significant predictors. The same model explained 11% of variance in SD (p=0.056) with ego-oriented motivation (b=-0.261, p=0.007) resulting as the only significant predictor. Again, the model explained 20% of variance in RSA (p